Tatbiq Ṭarīqat al-Kharīṭah al-Dhihniyyah fī Ta‘līm ‘Ilm al-Naḥw ladā Ṭullāb al-Ṣaff al-Thāmin Bayna MIPAS fī Madrasah al-Amīn al-Mutawassiṭah al-Islāmiyyah, Umbulu, Jember: The Application of the Mind Mapping Method in Teaching Arabic Grammar to Eighth-Grade Students in the MIPA Stream at Al-Amīn Islamic Junior High School, Umbulu, Jember - Elsa Mahdalena; Muh. Nidom Hamami Abicandra (Critical Review of English-Arabic World Journal is an open-access journal published by the Language Development Unit, State Islamic University of Kiai Haji Achmad Siddiq, Jember, 2025)
أظهر تطبيق طريقة الخريطة الذهنية في تعليم النحو العربي فوائد ملحوظة لدى طلاب الصف الثامن في برنامج BINA MIPAS بالمدرسة المتوسطة الإسلامية الأمين في أمبولو، جمبر. وبالمقارنة مع الصفوف الأخرى، أبدى طلاب BINA MIPAS مستوى أعلى من الكفاءة في فهم المفاهيم النحوية وتذكرها، ولا سيما في سياق الجمل الاسمية والفعلية. يهدف هذا البحث النوعي القائم على دراسة الحالة إلى وصف تطبيق طريقة الخريطة الذهنية في تعليم النحو العربي، مع التركيز على الجمل الاسمية والفعلية. جُمعت البيانات من خلال الملاحظة، والمقابلات، والتوثيق، وتم تحليلها باستخدام النموذج التفاعلي لمايلز وهوبرمان. كما أُجري التثليث في المصادر والتقنيات لضمان صدق البيانات. كشفت النتائج أن تطبيق طريقة الخريطة الذهنية مرّ بعدة مراحل، وهي: التهيئة، والفهم، ومراجعة المادة الدراسية، وتشكيل المجموعات، وعرض الخرائط الذهنية، والتقويم بعد نشاط الخريطة الذهنية، ثم الخاتمة. وقد ثبتت فاعلية هذه الطريقة في تعزيز فهم الطلاب للجمل الاسمية والفعلية والاحتفاظ بها، وتنمية قدراتهم الإبداعية والتعاونية. أما أبرز المعوقات التي تم تحديدها فتشمل محدودية وقت التدريس، وتفاوت القدرات المعرفية لدى الطلاب، وقلة الوسائل التعليمية، وصعوبة توقيت الحصة لكونها في الحصة الأخيرة من اليوم الدراسي. وعلى الرغم من هذه المعوقات، ظلت طريقة الخريطة الذهنية فعّالة بدرجة عالية في دعم طلاب الصف الثامن ببرنامج BINA MIPAS في إتقان الجمل الاسمية والفعلية في النحو العربي. The implementation of the Mind Mapping method in teaching Arabic grammar has demonstrated significant benefits for eighth-grade students of the BINA MIPAS program at Al Amin Islamic Middle School in Ambulu, Jember. Compared to other classes, BINA MIPAS students have shown higher proficiency in understanding and remembering grammatical concepts, especially in the context of nominal and verbal sentences. This qualitative, case study–based research aims to describe the implementation of the Mind Mapping method in teaching Arabic grammar, focusing on nominal and verbal sentences. Data were collected through observations, interviews, and documentation, and analyzed using the Miles and Huberman interactive model. Triangulation of sources and techniques was conducted to ensure data validity. The results reveal that the implementation of the Mind Mapping method progressed through several phases: initiation, comprehension, review of the lesson material, group formation, presentation of the mind maps, assessment after the Mind Mapping activity, and concluding remarks. The method proved effective in enhancing students’ understanding and retention of nominal and verbal sentences, fostering their creative and collaborative abilities. The primary constraints identified included limited instructional time, variations in students’ cognitive abilities, scarcity of teaching resources, and the challenge posed by scheduling the lesson in the final period of the school day. Despite these constraints, the Mind Mapping method remained highly effective in supporting eighth-grade BINA MIPAS students in mastering nominal and verbal sentences in Arabic grammar.